Bulk and clay mineralogy, elemental geochemistry and dinocyst assemblages of sediment core and composite sequence AMD0214-03 the Mackenzie Slope (Beaufort Sea, Canadian Arctic) - Omnain Kutos; André Rochon; Jean-Carlos Montero-Serrano (PANGAEA, 2026)
Bulk and clay mineralogy and elemental geochemistry, together with dinocyst assemblages, were investigated in order to reconstruct detrital inputs and to estimate sea-surface conditions related to late Holocene ocean-climate variability over the last 2000 years. A box core (BC) (AMD0214-03BC) and a trigger weight core (TWC) and piston core (PC) (AMD0214-03PC) were recovered from the Mackenzie Slope (Beaufort Sea, Canadian Arctic) and combined into a composite sequence (AMD0214-03CS).